Ministry in the margins: Thomas Swalwell, OSB, and his marginal notes for preaching on the clergy - Thayer, Anne T. (The sixteenth century journal, 2016)
Thomas Swalwell, OSB (d. 1539), monk of Durham, left significant marginalia in his many books. Well educated and reform minded, Swalwell's notes indicate his high expectations for the clergy. In addition, these notes suggest how he might have preached on this topic, using both the homily and the scholastic sermon style. Prelates and curates were to be engaged with those in their charge, not abuse their power, and live up to their callings. Swalwell held traditional views of the sacraments, but was aware of the contemporary challenges launched against transubstantiation and penitential good works. Preaching emerges as a central task for clergy, a vehicle for sharing the preacher's learning, engaging his audience, and counteracting heresy, especially as Luther's ideas begin to circulate.